Effects of Sonication Time on the Stability and Viscosity of Functionalized MWCNT-Based Nanolubricants - Dalkilic, Ahmet S.; Küçükyıldırım, Bedri Onur; Eker, Ayşegül Akdoğan; Yıldız, Faruk; Akpinar, Altuğ; Jumpholkul, Chaiwat; Wongwises, Somchai (Current Nanoscience, 2020)
Background: Active scholars in the nanofluid field have continuously attempted to remove the associated challenge of the stability of nanofluids via various approaches, such as functionalization and adding a surfactant. After preparing a stable nanofluid, one must measure the properties, as this is vital in the design of thermal systems. Objective: Authors aimed to investigate the stability and viscosity of refrigeration lubrication oilbased nanofluids containing functionalized MWCNTs. The effects of concentration and temperature on viscosity were studied. Furthermore, the present study focused on the effect of sonication time on the stability and viscosity of the prepared samples. Methods: After the preparation of chemically functionalized MWCNTs, solutions were dispersed with an ultrasonic homogenizer for 2, 4 and 8 hours sonication at maximum power. Viscosity measurements for all samples were made 10 minutes after sonication by adjusting the proper spinning velocity using a digital rotary viscometer. Results: The first part deals with the stability of the nanofluid as a nanolubricant, and the second one investigates the viscosity of the nanofluid and the effects of various parameters on it. The last one is related to the validation of the measured viscosity values by means of well-known empirical correlations. The measured data are given for validation issues. Conclusion: The samples will have higher stability by increasing the time of sonication. The viscosity of a nanofluid does not change with the increase of sonication time to two hours and higher. Up to mass concentration of 0.1%, the effective viscosity increases with adding nanotubes linearly.
Keywords: stability